Competency-Based Training Effectiveness Analysis “Meta Synthesis Of Training Components - Klara Septia Landa; Mustofa Kamil; Reza Gusmanti (Universitas Negeri Padang, 2022)
This research was conducted to synthesize a competency-based training process which was limited to the planning process. This research was conducted using the meta synthesis method on four research manuscripts on competency-based training. The results of the synthesis of the competency development process are gaps, there is no complete competency directory for each Department and the competency matrix for each employee is not yet complete, so that the design of technical competency development training does not fully refer to the standard criteria for behavior change that is expected to be displayed in their respective workplaces. units. the planning process is used as the beginning to conduct a training program, because the necessary needs must refer to the training needs analysis. In the process of implementing the design of training or employee competency training in order to improve employee performance in accordance with the objectives to be achieved. In the training evaluation process using pre-test and post-test, questionnaires to see the improvement in the implementation of the training program to see changes in behavior and employees after training